CONTROL INFORMATION BASED MICROCONTROLLER AT89C51 USING TELEPHONE HANDHELD - Agung Perdananto; Fivtatianti Fivtatianti. H, Skom, MM (Jurnal Sistem Komputer, 2007)
In writing that I make with the title "AT89C51 MICROCONTROLLER BASED CONTROL INFORMATION USING a mobile phone" is intended to be a system that can be used to control lighting with media that is already common cell phone and using AT89C51 microcontroller that can be developed further.